2011
DOI: 10.1088/0953-8984/23/32/325402
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigation of the negative thermal expansion in yttrium and rare earth molybdates

Abstract: The Sc(2)(WO(4))(3)-type phase (Pbcn) of Y(2)(MoO(4))(3), Er(2)(MoO(4))(3) and Lu(2)(MoO(4))(3) has been prepared by the conventional solid-state synthesis with preheated oxides and the negative thermal expansion (NTE) has been investigated along with an exhaustive structural study, after water loss. Their crystal structures have been refined using the neutron and x-ray powder diffraction data of dehydrated samples from 150 to 400 K. The multi-pattern Rietveld method, using atomic displacements with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
(122 reference statements)
4
6
0
Order By: Relevance
“…On the other hand, we have found that the less dense sample γ (dehydrated)-Ho 2 (MoO 4 ) 3 exhibits negative thermal expansion from 400 to 780 K, after water loss, as it is observed with other similar molybdates (Guzmán-Afonso et al, 2011) and from 1125 K to melting. We have calculated the linear thermal expansion coefficient α L (negative value) until 780K for γ-Ho 2 (MoO 4 ) 3 , and we have confirmed that α L is less negative when the ionic radius decreases (Guzmán-Afonso et al, 2011). The calculated value was -6.25x10 -6 K -1 ; thus, it shows the largest negative linear expansion coefficient for this family of compounds.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…On the other hand, we have found that the less dense sample γ (dehydrated)-Ho 2 (MoO 4 ) 3 exhibits negative thermal expansion from 400 to 780 K, after water loss, as it is observed with other similar molybdates (Guzmán-Afonso et al, 2011) and from 1125 K to melting. We have calculated the linear thermal expansion coefficient α L (negative value) until 780K for γ-Ho 2 (MoO 4 ) 3 , and we have confirmed that α L is less negative when the ionic radius decreases (Guzmán-Afonso et al, 2011). The calculated value was -6.25x10 -6 K -1 ; thus, it shows the largest negative linear expansion coefficient for this family of compounds.…”
Section: Resultssupporting
confidence: 59%
“…The β'-β phase transition is similar to other studied compounds: when the ionic radius decreases, the positive linear expansion coefficient is positive, although the c parameter decreases when the temperature increases . Negative thermal expansion has been found for the γ-phase, and the negative linear expansion coefficient decreases when the ionic radius decreases, as observed for similar compounds (Guzmán-Afonso et al, 2011). However, an anomalous behavior has been detected during the coexistence of phases.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…We used projector-augmented wave pseudopotentials [18,19] and the PBEsol prescription for the exchange and correlation energy within the generalized gradient approximation [20]. The 5s 2 , 5p 6 , 6d 1 , and 6s 2 electrons of La, the 5p 6 , 5d 4 , and 6s 2 of W, and the 2s 2 and 2p 4 of O were allowed to relax in the calculations, with the remaining electrons being kept frozen at the atomic cores. To ensure a total-energy convergence of 1 meV per formula unit, we used plane-wave basis sets with an energy cutoff of 520 eV and dense Monkhorst-Pack grids [21] appropriate for each structure considered-for example, a 4 × 4 × 2 grid (resulting in 20 independent k points) was used for the ambient-conditions α phase with two formula units in the primitive unit cell, and a 3 × 2 × 2 grid (eight k points) was used for the Bi 2 (MoO 4 ) 3 -type structure with four formula units in the unit cell.…”
Section: B Theoreticalmentioning
confidence: 99%
“…14, and Z = 4 are found in related compounds like Bi 2 (MoO 4 ) 3 , Sb 2 (SO 4 ) 3 , and As 2 (SO 4 ) 3 [1]. Trimolybdates and tritungstates with heavier RE cations (RE = Ho-Lu) adopt the γ form of Sc 2 (WO 4 ) 3 and display negative thermal expansion (NTE) [4][5][6]. A metastable ferroelectric phase with the β form of Gd 2 (MoO 4 ) 3 appears for intermediate * Corresponding author: javierl@marengo.dfis.ull.es molybdates with RE = Nd-Dy [4], but this has never been observed in tritungstates.…”
Section: Introductionmentioning
confidence: 99%